Delineating priority areas for marine biodiversity conservation in the Coral Triangle. (June 2018) - Asaad, Irawan; Lundquist, Carolyn J.; Erdmann, Mark V.; Costello, Mark J.
Abstract: Identifying priority areas for biodiversity conservation requires systematic approaches and integrated ecological and biological information. Here, we applied a range of ecological criteria to assess areas of biodiversity importance in the Coral Triangle region, a priority region for marine biodiversity conservation because of its high species richness and endemicity. We used distribution data of three biogenic habitats to assess the criterion of sensitive habitat, modeled geographic distributions of 10, 672 species ranges and occurrence records of 19, 251 species to evaluate the criterion of species richness, distributions of 834 species of special conservation concern to examine the criterion of species of conservation concern, distributions of 373 reef fish species to assess the criterion of restricted-range species, and distribution of nesting sites and migratory route of six species of sea turtle to evaluate the criterion of areas of importance for particular life history stages. We identified areas of biodiversity importance by superimposing each of the different criterion. We performed two tiers of multi-criteria analysis: (1) a Coral Triangle regional level analysis to identify "clustered hotspots" ( i . e ., groups of cells) of biodiversity significance, and (2) a site-based analysis to identify the specific sites (cells) of greatest biodiversity importance. We found that approximately 13% of the Coral Triangle was clustered into hotspots of high biodiversity importance. These areas occurred along the southern part of the Philippines, the north-eastern part of Malaysian Sabah, central to eastern reaches of Indonesia, the eastern part of Papua New Guinea and the Solomon Islands. By comparison, the site-based analysis identified seven sites of highest biodiversity importance in the Coral Triangle include: (1) the northern tip of Sulawesi Island, (2) Ambon Island, (3) Kei Islands, (4) Raja Ampat Archipelago of Indonesian Papua, (5) the Verde Island Passage, (6) the southern part of Negros Island, and (7) Cebu Island. This information is useful to inform participatory decision-making processes in the Coral Triangle region to identify priority areas for conservation and management. Highlights: We prioritized areas for marine conservation in the Coral Triangle region. The data used were species' ranges, occurrence records, habitat richness, threatened species, and sea turtle nesting sites. Nearly 13% of the Coral Triangle was clustered into areas of high biodiversity importance. The highest priority sites were the northern tip of Sulawesi, Ambon, Kei Islands, Raja Ampat Archipelago, in Indonesia; and Verde Island Passage, and the southern part of Negros and Cebu Islands, in the Philippines.